Stability Analysis of the Periodic Solutions of Some Kinds of Predator-Prey Dynamical Systems - Neslihan Nesliye Pelen (Journal of Mathematics, 2016)
Analysis of predator-prey dynamical systems that have the functional response which generalizes the other types of functional responses in two dimensions is mainly studied in this paper. The main problems for this study are to detect the if and only if conditions for attaining the periodic solution of the considered system and to find the condition for global asymptotic stability of this solution for some different types of predator-prey systems that are obtained from that system. To get the desired results, some aspects of semigroup theory for stability analysis and coincidence degree theory are used.